Antibiotic-induced gut microbiota dysbiosis and bile acid metabolism: implications for intestinal health, immune regulation, and disease susceptibility - Tareq Nayef AlRamadneh; Jasur Rizaev; Malathi Hanumanthayya; Maryam Abdul Al-Hussein; Ahmed Faisal Mutee; Mukhammadali Buriev; Nasiba Jumaniyazova; Shefali (Frontiers in Microbiology, 2026)
Intestinal microorganisms regulate bile acid (BA) homeostasis through bile salt hydrolase (BSH)-mediated deconjugation and a series of biotransformation reactions that generate secondary BAs with potent signaling functions. Antibiotic exposure profoundly disrupts these microbial processes, leading to alterations in BA composition, diversity, and enterohepatic circulation. Recent multi-omics studies have demonstrated that antibiotics reduce the abundance of key BA-transforming bacteria, including members of the Lachnospiraceae, Ruminococcaceae, Lactobacillaceae, Clostridiaceae, and Bacteroidaceae families, resulting in decreased BSH activity, depletion of secondary BAs, accumulation of conjugated primary BAs, and impaired BA signaling. Mechanistically, antibiotic-induced BA dysregulation affects several host regulatory pathways, including the farnesoid X receptor (FXR), Takeda G protein-coupled receptor 5 (TGR5), nucleotide-binding domain, leucine-rich–containing family, pyrin domain–containing-3 (NLRP3) inflammasome signaling, glucagon-like peptide-1 (GLP-1) secretion, and mammalian target of rapamycin (mTOR) signaling. Emerging evidence further suggests that BA metabolites serve as critical mediators linking antibiotic-induced dysbiosis with host hemostasis remodeling, T helper (Th)17-cell differentiation, and astrocyte activation, among others. These alterations contribute to diverse pathological outcomes, including loss of colonization resistance against Clostridium difficile , cholestatic liver injury, metabolic dysfunction, immune dysregulation, autoimmune inflammation, and gut–brain axis dysfunction. Conversely, selective manipulation of microbial BA metabolism may provide therapeutic benefits in specific disease contexts. Inhibition of microbial BSH activity by gentamicin alleviates experimental cholestasis, while microbiota-preserving narrow-spectrum antibiotics maintain secondary BA production and improve resistance to recurrent C. difficile infection. This review summarizes current evidence regarding the effects of antibiotics on microbial and molecular mechanisms driving BA imbalance, and discusses the implications of altered BA signaling for intestinal, hepatic, metabolic, immune, and neurological health.